Multicultural Education Through the Lens of Feminist Ethics and Its Implications in Indonesia - Hadi, Rahmad Tri; Putra, Rido; Meria, Aziza; Hakim, Lukmanul; Nursa, Ruri Afria (Kawanua International Journal of Multicultural Studies, 2025)
This paper is motivated by the problem of education development in Indonesia in the contemporary era, which overemphasizes competitive aspects but ignores aspects of multiculturalism and feminist ethics. This is certainly not in line with the principles of diversity that are embraced and will have an impact on the formation of characters that are exclusive, radical, give birth to various other socio-cultural deviations, and are not gender-friendly. This study aims to investigate the idea of multicultural education based on feminist ethics from Marilyn Friedman's point of view and assess its applicability to Islamic education in Indonesia. Employing a descriptive-analytical approach, the research draws primarily on Marilyn Friedman’s philosophical works, complemented by secondary sources such as books, academic journal articles, and relevant online materials discussing her ideas. The findings indicate that feminist ethics provides strong support for contemporary educational orientations that increasingly emphasize multiculturalism. Friedman conceptualizes this approach through several key stages: first, the articulation of feminist ethical justifications as the normative foundation of multicultural education; second, the continued integration of feminist ethics within multicultural curricula, emphasizing that multicultural education should actively address gender-based oppression, subordination, and marginalization rather than merely promoting awareness of diversity; and third, the necessity of critically resisting forms of moral arrogance originating from patriarchal, cultural, or religious frameworks in order to enhance the quality and inclusivity of multicultural education.